Guía metodológica para la administración de proyectos de vivienda transitoria en la Subdirección de infraestructura comunitaria de la organización TECHO Costa Rica - Silesky-Hernández, Bernhard; Henriquéz-Cruz, David (Instituto Tecnológico de Costa Rica, 2016)
This graduation project was carried out in the non-profit organization TECHO, with the aim of providing a methodological guide for the management of transitional housing construction projects, based on standards and recommended best practices of the Project Management Institute. The methodology guide was created based on the diagnosis of transitional housing projects carried out by the Community infrastructure branch, where a number of gaps were found regarding best practices and personal skills. These gaps provided inputs for the proposed processes, key elements, tools and templates, which are needed to effectively plan projects of this branch. Finally, an implementation guide is offered, which includes the steps and most important elements to get the methodology guide into the projects of the organization.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2016.
Keywords: Asentamientos; Voluntariado; Infraestructura; Construcción; Procesos; Organización; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture